EFFECTIVENESS OF USE OF PMRI APPROACH (REALISTIC MATH EDUCATION IN INDONESIA) ON RESULTS OF LEARNING MATHEMATICS STUDENTS IN SMP MUHAMMADIYAH 2 KALASAN - Tri Apualinayati; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2017)
This research was conducted on the grounds that there were still many students who were less active and initiative in making decisions to solve problems because students only copied from the teacher's example and waited for the teacher's instructions to solve the problems. This study aims to determine the effectiveness of the use of the PMRI Approach (Indonesian Realistic Mathematics Education) Against Mathematics Learning Outcomes of Class VIII Students of SMP Muhammadiyah 2 Kalasan Sleman Regency Even Semester Academic Year 2015/2016. The research design uses Posttest-Only Control Design. The population in this research is the eighth-grade students of SMP Muhammadiyah 2 Kalasan. The research sample was taken using a random sampling technique obtained by class VIII D as an experimental class and VIII B as a control class. Data collection is done by the test method. The instrument testing used validity tests, different power tests, and reliability tests. Data analysis techniques using analysis prerequisite tests include normality test with Chi-Square formula, homogeneity test with Bartlett test, and hypothesis testing with t-test. Based on calculations of the significant level Â and 67 degrees of freedom could be concluded that: (1) there were different result of Mathematics study between the students who used the learning of PMRI approach and the students who used traditional learning approach. This case showed from the result of the first hypothesis test is . (2) learning by using the PMRI approach more effective than using a traditional learning approach. This case showed from the result of the second hypothesis test is .